Modification of Sorghum Starch-Cellulose Bioplastic with Sorghum Stalks Filler - Darni, Yuli; Dewi, Febrina Yohana; Lismeri, Lia (Jurnal Rekayasa Kimia & Lingkungan, 2017)
This study evaluated the feasibility of bioplastics production by various ratio of sorghum starch and cellulose from red seaweed Eucheuma spinossum, and the use of glycerol as plasticizer and sorghum stalks as filler. Solid-liquid matrix transition should be far over the operating temperature of gelatinization and extracted at 95oC in order to avoid the loss of conductivity. The analyzed variables were starch and cellulose seaweed Eucheuma spinossum and the addition of variation of filler. Sorghum stalk could be expected to affect the mechanical and physical properties of bioplastics. A thin sheet of plastic (plastic film) was obtained as a result that have been tested mechanically to obtain the best condition for the formulation of starch-cellulose 8.5:1.5 (g/g). From the result of morphological studies, the fillers in the mixture composites were more randomly in each product and the addition of filler can increase mechanical properties of bioplastics. Chemical modication had a major effect on the mechanical properties. The phenomena of degradation and thermoplasticization were visible at chemical changes that can be observed in FTIR spectrum test results.